GUIDA: A Graphical User Interface for Optical Data Analysis of Isolated Pulsars. (4th January 2016) - Ambrosino, F.
Abstract: Studying pulsars from ground-based telescopes needs data analysis to be performed according to specific requirements. Because of the periodic behavior of these objects such requirements are expressed in terms of timing. In fact, several factors must be taken into account to correctly extract the period (frequency) and then light curves of pulsars. Until now, analysis software packages have been mainly developed for satellite data and are not completely suitable for optical observations from the ground. A software package called GUIDA has been developed to analyze optical photometric data recorded by the SiFAP instrument, completely conceived and realized at the Physics Department of La Sapienza-Università di Roma. This software package is capable of analyzing data relative to ground observations, including timing corrections, and of deriving corrected pulsar light curves.